Enhanced muscle nutrient content and flesh quality, resulting from tryptophan, is associated with anti-oxidative damage referred to the Nrf2 and TOR signalling factors in young grass carp (Ctenopharyngodon idella): Avoid tryptophan deficiency or excess. (15th May 2016) - Jiang, Wei-Dan; Wen, Hai-Lang; Liu, Yang; Jiang, Jun; Wu, Pei; Zhao, Juan; Kuang, Sheng-Yao; Tang, Ling; Tang, Wu-Neng; Zhang, Yong-An; Zhou, Xiao-Qiu; Feng, Lin
Graphical abstract: Highlights: Tryptophan (Trp) enhances muscle nutrient content and flesh quality in fish. Trp-enhanced flesh quality is related to inhibition of muscle oxidation in fish. The inhibition of muscle oxidation by Trp is due to increases of GSH and GPx. Muscle GPx activity increasing by Trp refers to Nrf2 and TOR signalling in fish. The Trp requirements for fish flesh quality were evaluated. Abstract: Flesh quality, muscle antioxidant status and related signalling molecule expressions were investigated in young grass carp fed six levels of tryptophan (Trp) for 8 weeks. The results indicated that fish fed 0.7 (deficiency) and 6.1 g Trp g/kg (excess) diets exhibited lower muscle water-holding capacity, tenderness, cathepsin activity, protein levels, lipids and collagen contents. Optimal Trp reversed these negative effects, which were related to enhanced glutathione (GSH) content and glutathione peroxidase (GPx) activities regulated at gene transcription levels, rather than to superoxide dismutase (SOD) or catalase (CAT). The expression of signalling molecules [Kelch-like ECH-associated protein 1, target of rapamycin (TOR) and ribosomal S6 protein kinase 1] involved in the NF-E2-related factor 2 (Nrf2) pathway revealed a potential method of Trp-enhanced antioxidant defence. Collectively, the present study indicated that appropriate Trp levels improved flesh quality partly related to the enhancement of antioxidant ability through Nrf2 and TOR signalling.